The Wedding at the Hotel: Venue Choice, Servicescape and Customer Experience as Shared on TripAdvisor - Sanches Cartas, Beatriz; Guerreiro, Manuela; Barreira, Ana Paula (Journal of Tourism, Sustainability and Well-being, 2025)
A wedding is always a special event. The wedding experience, carved under the influence of environmental stimuli – servicescape or wedding-scape – and an antecedent of behavioural outcomes, as shared in online platforms, increasingly influences the decision-making of other couples. Adopting an experiential Marketing perspective of the wedding as a staged experience and framed by the Stimulus-Organism-Response (S-O-R) paradigm, this study aims to investigate venue choice criteria, servicescape/wedding-scape attributes, experience, and behavioural outcomes related to wedding ceremonies performed at the hotel venue as shared in social media. A thematic content analysis was performed on the 173 comments gathered from TripAdvisor. These reviews were shared by the bride and groom and their guests who had their wedding at a five-star Hotel Resort located in the Algarve, south of Portugal. The study reveals positive perceptions of venue conditions, location, staff, and cleanliness, alongside negative evaluations of price and styling, shaping guests’ cognitive and affective responses, ultimately fostering memorable wedding experiences and high recommendation intentions at Tivoli Resort.